(untitled) (Eurasian Medical Research Periodical, 2023)
Numerous studies of cardiovascular diseases from the perspective of the cardiovascular continuum indicate the leading role of the imbalance of the neurohumoral system in favor of the increased activity of its sympatho-adrenal and angiotensin-adrenal components. Methods for assessing these vital regulators are very diverse, each of them has its own advantages and disadvantages.